Low Intelligence Predicts Higher Risks of Coronary Artery Disease and Myocardial Infarction: Evidence From Mendelian Randomization Study - Yang, Fangkun; Hu, Teng; Chen, Songzan; Wang, Kai; Qu, Zihao; Cui, Hanbin (Frontiers in Genetics, 2022)
Background: Low intelligence has been shown to be associated with high risk of cardiovascular disease in observational studies. It remains unclear whether the association is causal. This study aimed to explore the causal association of intelligence with coronary artery disease and myocardial infarction. Methods: A two-sample Mendelian randomization study was designed to infer the causality. A total of 121 single nucleotide polymorphisms were selected as genetic instrumental variable for intelligence. Summary data on coronary artery disease (n = 184,305) and myocardial infarction (n = 171,875) was obtained from the Coronary ARtery DIsease Genome wide Replication and Meta-analysis (CARDIoGRAM) plus The Coronary Artery Disease (C4D) Genetics (CARDIoGRAMplusC4D) consortium. Inverse variance weighting method was used to calculate the effect estimates. Sensitivity analyses including other statistical models and leave-one-out analysis were conducted to verify the robustness of results. MR-Egger test was performed to assess the pleiotropy. Results: Genetically predicted higher intelligence was significantly associated with lower risk of coronary artery disease (OR, 0.76; 95%CI, 0.69-0.85; p = 1.5×10-7) and myocardial infarction (OR, 0.78; 95%CI, 0.70-0.87; p = 7.9×10-6). The results remained consistent in the majority of the sensitivity analyses. MR-Egger test suggested no evidence of directional pleiotropy for the association with coronary artery disease (Intercept = -0.01, p = 0.19) and myocardial infarction (Intercept = -0.01, p = 0.06). Conclusions: This Mendelian randomization analysis provided genetic evidence for the causal association between low intelligence and increased risks of coronary artery disease and myocardial infarction.